The pathogenesis of dementia praecox - Holmes, Bayard (1921)
Many authors have clearly shown that dementia praecox is always associated with profound anatomical and histopathological lesions. Ranaudie work is an admirable summary of these findings. CV Kitabayashi and S. Monakov and have more recently shown that the choroid plexus is affected, so inflamed and atrophied uniform dementia praecox.